Differentiated ratings of perceived exertion between overweight and non-overweight children during submaximal cycling - Laurent, C. Matthew; Green, J Matthew; Davis, Jon-Kyle; Geary, Colleen L.; Voth, Nicholas R. (International Journal of Health Sciences, 2018)
Objective: Few studies have examined differences in ratings of perceived exertion (RPE) between overweight (OW) and non-OW (NW) youth. With lower voluntary participation in physical activity in OW children, it seems plausible that these youth may experience elevated RPE. Therefore, this study compared RPE during two separate steady-state cycling bouts OW (>95th body mass index [BMI] percentile) and NW (<90th BMI percentile) children. Methods: Participants completed one of two 20-min cycling trials; one performed at 70% age-predicted peak heart rate (HR) (70%) (OW n = 12 and NW n = 21) and a self-selected intensity (SS) (OW n = 6 and NW n = 13) with RPE overall, RPE legs (RPE-L), and RPE chest estimated at 5, 10, 15, and 20 min. Results: A repeated measures ANOVA revealed that OW individuals had significantly lower RPE-L values at 5, 15, and 20 min during the SS trial. No significant differences were identified during the 70% trial. Conclusions: OW youth do not perceive cycling at 70% age-predicted peak HR or at SS intensities more difficult than NW children. It may be that cycling could serve as an attractive mode to encourage physical activity in this population and perhaps increase self-efficacy of exercise in this population. Conclusions: OW youth do not perceive cycling at 70% age-predicted peak HR or at SS intensities more difficult than NW children. It may be that cycling could serve as an attractive mode to encourage physical activity in this population and perhaps increase self-efficacy of exercise in this population. Keywords: Body mass index, children, perception of effort, physical activity